The Role of the New Anti-CD20 Monoclonal Antibodies in Active Relapsing – Remitting Multiple Sclerosis Treatment: Efficacy and Safety of ofatumumab - Jonušaitė, I.; Giedraitienė, N.; Kaubrys, G.; Kizlaitienė, R. (Neurologijos seminarai, 2024)
Multiple sclerosis is the most common chronic demyelinating neurodegenerative central nervous system disease among young adults. Considering its extent in a relatively young population, multiple sclerosis determines a significant socioeconomic burden to the society due to the cost of disease modifying treatment and a lower working capacity of patients and their caregivers. It is important to control neuroinflammation in the central nervous system caused by the pathologic activity of immune cells by considering a high efficacy treatment early in the disease course in order to prevent accumulation of neurological damage and to improve long term outcomes. According to the newest clinical studies, anti-CD20 therapies have proven their effectiveness and safety in active relapsing multiple sclerosis treatment: since 2018, ocrelizumab, and, since 2023, ofatumumab have both been available as treatment options in Lithuania. Because of its high potency and safety, as well as the specific mechanism of action, ofatumumab is effective in lower doses, and, after initial training at a health care facility, it can be self-administered through subcutaneous injection. This article reviews the efficacy, safety data and treatment indications of the latest available anti-CD20 monoclonal antibodies.
Keywords: multiple sclerosis; economic burden; anti-CD20 therapy; monoclonal antibodies; ofatumumab